PENERAPAN "BALANCED SCORECARD" PADAANALISIS KELAYAKKAN SISTEM INFORMASI UNTUK ORGANISASI PEMERINTAH - Sari, Putri Pradnyawidya (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2012)
Information systems are now a staple in the organization in supporting the implementation of operational activities. Application of information technology systems would be beneficial if the application in accordance with the objectives, vision and mission of the organization by implementing a strategy of information technology systems. The purpose of this paper is to provide insight for the perpetrators in government organizations in analyzing kelayakkan to an information system. In developing this paper information system using the theory of Balanced Scorecard. Stages of planning begins with determining the goals of the organization in implementing an information system. Surabaya BPPKI balanced scorecard uses four perspectives to address the needs of service desired. By applying the Balanced Scorecard can help actors in government agencies to determine that an information system is feasible.